Symptoms and the body: Taking the inferential leap - Van den Bergh, Omer; Witthöft, Michael; Petersen, Sibylle; Brown, Richard J. (Neuroscience and biobehavioral reviews, 2017)
•The experience of physical symptoms is related to physiological dysfunction in a highly variable way.•Using a predictive coding framework we propose a new model of the body-symptom relationship.•We describe critical conditions influencing the body-symptom correspondence.•Theoretical and clinical implications of this new account are explored. The relationship between the conscious experience of physical symptoms and indicators of objective physiological dysfunction is highly variable and depends on characteristics of the person, the context and their interaction. This relationship often breaks down entirely in the case of “medically unexplained” or functional somatic symptoms, violating the basic assumption in medicine that physical symptoms have physiological causes. In this paper, we describe the prevailing theoretical approach to this problem and review the evidence pertaining to it. We then use the framework of predictive coding to propose a new and more comprehensive model of the body-symptom relationship that integrates existing concepts within a unifying framework that addresses many of the shortcomings of current theory. We describe the conditions under which a close correspondence between the experience of symptoms and objective physiology might be expected, and when they are likely to diverge. We conclude by exploring some theoretical and clinical implications of this new account.